Serotype Distribution and Antimicrobial Susceptibility Pattern of Streptococcus pneumoniae in COVID-19 Pandemic Era in Brazil - Samanta C. G. Almeida; Ana Paula S. de Lemos; Ana Luiza Bierrenbach; José Cássio de Moraes; Maria Cristina de Cunto Brandileone (Microorganisms, 2024)
Despite the introduction of the pneumococcal vaccine, Streptococcus pneumoniae remains a cause of invasive diseases in Brazil. This study provides the distribution of serotypes and antimicrobial susceptibility patterns for pneumococcal isolates before and during the years of the COVID-19 pandemic in two age groups, <5 and ≥50 years. This is a national laboratory-based surveillance study that uses data from the Brazilian national laboratory for invasive S. pneumoniae from the pre-COVID-19 (January 2016 to January 2020) and COVID-19 (February 2020 to May 2022) periods. Antimicrobial resistance was evaluated by disk diffusion and minimum inhibitory concentration. The year 2020 was marked by a 44.6% reduction in isolates received and was followed by an upward trend from 2021 onwards, which became evident in 2022. No differences were observed in serotypes distribution between the studied periods. The COVID-19 period was marked by the high prevalence of serotypes 19A, 3, and 6C in both age groups. Serotypes 19A and 6C were related to non-antimicrobial susceptibility. We observed a reduction in S. pneumoniae, without changes in serotypes distribution and epidemiological capsular switch during the COVID-19 period. We observed elevated resistance rates, mainly to penicillin and ceftriaxone for non-meningitis cases in children under 5 years of age.